2021
DOI: 10.1111/1556-4029.14906
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the decomposition process of shallow graves on soil mite abundance

Abstract: Burial of a cadaver results in a slower decomposition rate, due to more stable belowground temperatures and restricted access to necrophagous insects. In such circumstances, analysis of the soil mesofauna, with emphasis on mites (Acari) may be more valuable in time-of-death estimations. The production of volatile organic compounds of cadaveric decay results in changes, especially in the soil pH, which in turn would affect the abundance and diversity of the associated mites. In general, the effects of decomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…It has been found that corpses buried in shallow graves (<30 cm) decompose faster than those buried at greater depths. This discrepancy results from the thinner layer of soil, which offers less protection from environmental factors and temperature fluctuations [8,28,29]. To investigate the effects of burial on chondrocyte viability, 50 cm deep graves were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that corpses buried in shallow graves (<30 cm) decompose faster than those buried at greater depths. This discrepancy results from the thinner layer of soil, which offers less protection from environmental factors and temperature fluctuations [8,28,29]. To investigate the effects of burial on chondrocyte viability, 50 cm deep graves were used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…1-A) (Rai et al, 2021). Despite being buried superficially, the occurrence and abundance of mite species are mainly dictated by the composition and chemistry of the soil and by the surrounding soil pH (Rai et al, 2022). Any arthropod species will inform about their part in the decomposition process; providing reliable evidence of what has happened to the victim just before and during death, about where death occurred, and, if there was a relocation of the corpse, explaining with their life cycles why and how a person died, linking environments, locations and people (Perotti & Braig, 2020).…”
mentioning
confidence: 99%